2021
DOI: 10.1371/journal.pone.0247809
|View full text |Cite
|
Sign up to set email alerts
|

Effects of foliar fungicide on yield, micronutrients, and cadmium in grains from historical and modern hard winter wheat genotypes

Abstract: Plant breeding and disease management practices have increased the grain yield of hard winter wheat (Triticum aestivum L.) adapted to the Great Plains of the United States during the last century. However, the effect of genetic gains for seed yield and the application of fungicide on the micronutrient and cadmium (Cd) concentration in wheat grains is still unclear. The objectives of this study were to evaluate the effects of fungicide application on the productivity and nutritional quality of wheat cultivars r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 80 publications
2
4
0
Order By: Relevance
“…The concentrations of Cu, Fe, Ni, Mn, Zn, Ca, and K measured in grains in the base zone (Table ) were in line with or slightly higher than those commonly reported for wheat grains. , The concentrations of Cu, Mn, Ni, Ca, and K decreased ( p < 0.05) with increased soil Cd content, on average by respectively, 35, 54, 44, 13, and 18%, between Cd0.1 and Cd10, whereas the concentrations of Fe and Zn were not affected ( p > 0.05) by the Cd treatment. As observed for Cd (see above), the concentrations of Mn, Zn, and Ca in the grains in the base zone were higher ( p < 0.05) in Fusarium-infected than in mock-inoculated plants, by an average of 56% for Mn, 51% for Zn, and 13% for Ca, while the concentrations of the four other elements were not affected ( p > 0.05) by Fusarium infection.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The concentrations of Cu, Fe, Ni, Mn, Zn, Ca, and K measured in grains in the base zone (Table ) were in line with or slightly higher than those commonly reported for wheat grains. , The concentrations of Cu, Mn, Ni, Ca, and K decreased ( p < 0.05) with increased soil Cd content, on average by respectively, 35, 54, 44, 13, and 18%, between Cd0.1 and Cd10, whereas the concentrations of Fe and Zn were not affected ( p > 0.05) by the Cd treatment. As observed for Cd (see above), the concentrations of Mn, Zn, and Ca in the grains in the base zone were higher ( p < 0.05) in Fusarium-infected than in mock-inoculated plants, by an average of 56% for Mn, 51% for Zn, and 13% for Ca, while the concentrations of the four other elements were not affected ( p > 0.05) by Fusarium infection.…”
Section: Resultssupporting
confidence: 84%
“…In cereal grains, micronutrients (e.g., Fe and Zn) and toxic trace metals such as Cd and Pb are preferentially stored in the peripheral aleuronic layer rather than in the starchy endosperm. Consequently, their concentration in the grain usually decreases with an increase in grain size, which is mainly due to the increase in endosperm. This is one reason for the “dilution effect” described for micronutrients in wheat grains . The relationship between the sink strength for photoassimilates and the concentration of Cd in grains relies on potential decoupling between the allocation of Cd and photoassimilates to the grain.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the use of fungicides is expensive which a problem is for poor farmers (Ali et al, 2021). Recent studies indicated that the impact of foliar rusts on wheat quality and plant development depends on the level of genotype resistance, yield potential and onset of disease (Herrera-Foessel et al, 2006;Cruppe et al, 2021;Motta-Romero et al, 2021). Ash and Brown (1990) exhibited that an early outbreak of disease percentage had a larger effect on grain yield as compared to the late epidemics.…”
Section: Discussionmentioning
confidence: 99%
“…Higher concentrations of the toxic metal Cd in conventional wheat grain were linked to higher inputs of mineral P fertilizers (which contain Cd) [ 111 ], but recent variety trials with spring and wheat also identified significant main effects of variety [ 57 , 112 ] (see Table 7 for an example).…”
Section: Breeding/selection Methods Strategies and Approachesmentioning
confidence: 99%